Body burden and influencing factors of polychlorinated dibenzodioxins and dibenzofurans (PCDD/Fs) in male workers from a municipal waste incineration plant in China - Peng, Jinling; Jiang, Yousheng; Ai, Chunyan; Liu, Yuan; Lin, Xiaoshi; Zhou, Jian; Zhang, Jianqing (Environmental pollution (1987), 2022)
Emissions of polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans (PCDD/Fs) from municipal solid waste incinerators (MSWIs) have aroused public concern around the world. However, biomonitoring evidence regarding the influence of MSWIs on the human body burden of PCDD/Fs is scarce. The aim of this study is to investigate the human body burden levels of PCDD/Fs in MSWI workers and to further explore the potential influencing factors, including duration of occupation and dietary habits, on the PCDD/F levels. A total of 98 paired serum samples from MSWI workers and non-MSWI workers were collected. Seventeen 2,3,7,8-chlorine substituted PCDD/Fs in the serums were analyzed using an isotope dilution high-resolution gas chromatograph/high-resolution mass spectrometer (HRGC/HRMS). The results showed that the mean levels of toxic equivalent (TEQ)-PCDD/Fs for the MSWI workers and the control group were 18.28 pg TEQ g−1 lipid and 5.81 pg TEQ g−1 lipid, respectively. Significantly higher concentrations of PCDD/Fs existed in the incinerator workers compared with the control subjects after adjustment of the confounding factors. OCDD was the most abundant congener in both the MSWI workers and the control subjects, accounting for 82.2% and 89.4% of the ∑17PCDD/Fs, respectively. The serum levels of PCDFs in the MSWI workers increased with the duration of occupation (β = 0.498, P = 0.031), and a higher total concentration of PCDD/Fs were present in senior workers classified as production supervisors than routine operation staff (β = 8.809, P = 0.008). No significant relationship was found between the PCDD/F concentrations and dietary habits. This study was the first to explore the associations between the body burden of PCDD/Fs and occupational exposure as well as dietary intake of MSWI workers in China. The findings provide scientific information for health risk assessments of human exposure to PCDD/Fs. [Display omitted] •Higher body burden of PCDD/Fs was found in the MSWI workers than the control subjects.•Duration of occupation was positively associated with body burden of PCDD/Fs in the MSWI workers.•Occupational exposure was the dominant factor for higher serum PCDD/F levels in the MSWI workers.•The findings provided scientific information for the future management of MSWIs in China.